2013
DOI: 10.3109/01658107.2013.785573
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Idiopathic Intracranial Hypertension With Malignant Systemic Hypertension—A Case Report

Abstract: We describe a young woman who presented with malignant systemic hypertension and fulminant idiopathic intracranial hypertension. This is a rare combination, but both diagnoses should be considered in patients with optic disc swelling in whom cerebral imaging does not suggest an alternative cause. In this case, malignant hypertension was identified and treated before the idiopathic intracranial hypertension was recognised. Visual failure was evident at presentation and prior to blood pressure manipulation. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Abbasi et al reported a young female who was found to have malignant hypertension and later to have intracranial hypertension. 2 The authors in this case also argue for LP in patients presenting with bilateral disc edema in the setting of severe hypertension.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Abbasi et al reported a young female who was found to have malignant hypertension and later to have intracranial hypertension. 2 The authors in this case also argue for LP in patients presenting with bilateral disc edema in the setting of severe hypertension.…”
Section: Discussionmentioning
confidence: 74%
“…1 Intriguingly, (i) the majority of subjects harbouring mtDNA mutations do not develop visual symptoms, (ii) a striking number of LHON patients have no family history, and (iii) there is significant male predominance (male:female,~3:1). [1][2][3] These observations suggest significant variability in disease penetrance and point to a complex disease model with interacting environmental and genetic factors.…”
Section: Late-onset Leber Hereditary Optic Neuropathy Presenting Aftementioning
confidence: 94%
“…4 Fulminant IH (FIH) is a special designation for cases in which 4 weeks or less pass between onset of IH signs and symptoms and severe visual loss, or there is rapidly worsening visual loss over a few days' time. 5,6 The patient in our case meets the criteria of FIH using the latter definition.…”
Section: Discussionmentioning
confidence: 85%
“…One of the leading theories into the pathophysiology of IH is excess inflammation, supported by studies which have demonstrated increased rates of IH in inflammatory diseases such as systemic lupus erythematous (SLE) and Sjogren's syndrome (SS). 3,5 Other larger studies which have demonstrated exposure to infectious and inflammatory disorders were three to four times more common in the 12 months prior to an IH diagnosis when compared with controls. 3,13 Given the general absence of SARS-CoV-2 from CSF in patients with disease, a systemic reaction with resultant IH is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Given the severity of the optic nerve head edema, we postulated that the patient’s intracranial hypertension may have been exacerbated by the systemic hypertension. Elevated intracranial pressure with papilledema and concomitant hypertensive emergency is a rare clinical scenario, described only once previously to our knowledge, and the nerve edema from either is not readily distinguishable from the other . An incomplete workup can easily result in treatment of only 1 of the conditions, leading to continued visual deterioration and possible permanent damage from delay in appropriate treatment, showing again that choice D is necessary.…”
Section: Discussionmentioning
confidence: 99%